Recent Publications (Quarterly Journal of Economics, 1964)
Recent Publications Get access The Quarterly Journal of Economics, Volume 78, Issue 2, May 1964, Pages 350–353, https://doi.org/10.1093/qje/78.2.350 Published: 01 May 1964